High Gain Interleaved Boost Converter for Fuel Cell Applications - R. Seyezhai; R. Anitha; S. Mahalakshmi; M. Bhavani (Institute of Advanced Engineering and Science, 2013)
Fuel cell is one of the promising technologies for distributed generation. For designing high efficiency fuel cell power systems, a suitable DC-DC converter is required. Among the various topologies, interleaved converters using switched capacitor are considered as a better solution for fuel cell systems due to high conversion efficiency. The objective of the paper is to design and implement a high gain interleaved converter using switched capacitors for fuel cell systems. In the proposed interleaved converter, the front end inductors are magnetically cross-coupled to improve the electrical performance and reduce the weight and size. Also, switched capacitors are used to improve the voltage gain of the converter. The proposed converter has been performed. Simulation study of interleaved converter using switched capacitors interfaced with fuel cells has been studied using Matlab/Simulink. A prototype has been developed to verify the simulation results.